Dahuang Zhechong Pill suppresses colorectal cancer liver metastasis via ameliorating exosomal CCL2 primed pre-metastatic niche. (28th June 2019) - Chen, Chunhui; Yao, Xueqing; Xu, Yihua; Zhang, Qingyuan; Wang, Hao; Zhao, Liang; Wen, Ge; Liu, Yawei; Jing, Linlin; Sun, Xuegang
Abstract: Ethnopharmacological relevance: Dahuang Zhechong Pill (DZP) is a classical formula from "Synopsis of Prescriptions of the Golden Chamber". It has been used for treatment of abdominal masses (including tumorous diseases) for thousands of years. Aim of the study: Our previous work showed that DZP suppresses CCl-4 induced hepatic fibrosis by downregulating the expression of interleukin-13. We aimed to test if DZP suppresses the metastasis of colorectal cancer (CRC) by ameliorating the fibrosis status of the future metastatic organ. Materials and methods: Liver metastasis was observed by injection of MC38-EGFP cells with stably expressing enhanced green fuorescence protein beneath the splenic capsule of C57BL/6J mice. MC38-EGFP-derived exosomes were analyzed by Label-free comparative proteomics. mRNA expression was determined by Quantitative PCR. Protein expression was determined by immunohistochemistry, immunofuorescence and Western blot. Collagen deposition was determined by Masson staining. All data were statistically analyzed using SPSS. Results: DZP drastically reduced the metastatic tumor number and fluorescence intensity in a splenic liver metastasis model. It also lowered the expression of mature TGF-β1 and decreased the fibronectin contents & collagen deposition. Exosome proteomics showed that the upregualted CC chemokine ligand-2 (CCL2) was repressed by DZP treatment. Importantly, DZP markedly lowered the expression of CCL2 and its receptor CCR2 in the liver. Exosomal CCL2 activated macrophage recruitment and shifted the M1/M2 paradigm to a M2 phenotype. DZP reduced the macrophage infiltration and attenuated the M2 polarizaion in tumor-bearing mice liver. It decreased the F4/80 positive areas and specifically reduced the ratio of CCR2 + positive macrophage. Anti-fibrosis and inhibition of CCR2 suppress the growth and metastasis of CRC. Conclusions: DZP inhibits the liver metastasis of CRC by suppressing CCL2 mediated M2-skewing paradigm and ameliorating the pro-fibrotic microenvironment. Graphical abstract: Image 1